Xp21 DNA microdeletion syndrome in a Chinese family: clinical features show retinitis pigmentosa and chronic granuloma - Li, Mengyang; Hu, Xueqin; Wu, Xueli; Zhao, Na; Lian, Yuanyuan; Ma, Meijiao; Li, Huiping; Sheng, Xunlun (Frontiers in Genetics, 2024)
Xp21 DNA microdeletion syndrome is a very rare disease characterized by retinitis pigmentosa (RP), chronic granulomatous disease (CGD), and McLeod syndrome (MLS). Due to the complex and diverse clinical manifestations, early diagnosis remains a challenge for many physicians. In this study, for the purpose of determining the pathogenic gene variants and definitive diagnosis in a patient medically backgrounded with RP and CGD from a normal Chinese family, whole-exome sequencing (WES) was performed in this proband and copy number variation (CNV) was further verified in other family members by qPCR. A genetic evaluation revealed that the short arm of the X chromosome in the proband had a deletion CNV Xp21.1p11.4 (37431123–38186681) of approximately 0.755 Mb in size, and contained three contiguous OMIM genes as X-linked Kx blood group antigen (XK), cytochrome b-245 beta chain (CYBB), and RP GTPase regulator (RPGR). The qPCR results confirmed the copy number loss in Xp21.1p11.4 present in the proband and his unaffected mother. According to the American College of Medical Genetics and Genomics (ACMG) guidelines for the CNV interpretation, the deletion of this segment was a pathogenic variant. Our results provided evidence that CNV deletion of Xp21.1p11.4 in the short arm of the X chromosome was a pathogenic variant in such Chinese RP and CGD family, and the McLeod phenotype was not yet available. This study suggests that genetic testing is essential for a definitive diagnosis, which should better assist physicians in prediction, diagnosis, genetic counseling, and guidance for Xp21 DNA microdeletion syndrome.